Relationship between parents, peer, lecturer attachment and Islamic resiliency among University Putra Malaysia students - Hamsan, Hanina Halimatusaadiah (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The main purpose of this study is to determine the relationship between parents,peer, lecturer attachment and resiliency among UPM students. Three factors which are parents, peer and lecturer attachment have been studied about their relationship with resiliency. A total of 397 undergraduates students in UPM were selected through convenience sampling as respondents in this study. Inventory of Parents and Peer Attachment (Armsden and Greenberg, 1987) was used to measure the level of parents and peer attachment, followed by Inventory of Teacher-Student Relationships (Murray and Zvoch, 2011) to measure the level of lecturer attachment and Adolescent Resilience Scale (Oshio, Kaneko, Nagamine & Nakaya, 2003) to assess the level of students’ resiliency. The results of this study show that most of the respondents perceived moderate level of resiliency (M = 78.18; SD = 7.697), peer attachment (M = 101.27; SD = 13.283) and lecturer attachment (M = 45.46; SD =9.096), and high level of parents attachment (M = 103.22; SD = 11.495). The findings revealed that there was significant relationship between parents attachment (r = 0.434; p = 0.000), peer attachment (r = 0.455; p = 0.000), lecturer attachment (r =0.495; p = 0.000) and resiliency. The result from the study shows that the importance of improving the level of resiliency among the students in university is increasing the attachment to students’ parents, peer, and lecturer in order to become the good student in the life.